The impact of the exchange rate and money supply on the promotion of non-hydrocarbon exports in Algeria during the period (1990-2022) - bouzerkoula, Abdelhamid; djedi, Larbi; chermat, Tahar (Journal of Excellence for Economics and Management Research, 2024)
This study aimed to measure the impact of monetary policy tools represented by the exchange rate and the money supply in its broad sense in promoting non-hydrocarbon exports in Algeria during the period 1990-2022, based on the FARDL model. The study concluded that there is a long-term equilibrium relationship between the study variables; as the increase in the money supply leads to an increase in non-hydrocarbon exports, while there is a negative impact of the exchange rate in promoting non-hydrocarbon exports.